Fruit development and seed dispersal - Ostergaard, Lars (Ames, Iowa : Wiley-Blackwell, 2010)
"Fruit development and seed dispersal are major topics within plant and crop sciences research with important developments in research being reported regularly. Drawing together reviews by some of the world's leading experts in these areas, the Editor of this volume, Lars Ostergaard has provided a volume which is an essential purchase for all those working in plant and crop sciences worldwide". --Balogh Interenational.
1. Carpel evolution -- 2. Gynoecium patterning in Arabidopsis: a basic plan behind a complex structure -- 3. The ins and outs of ovule development -- 4. Fertilisation and fruit initiation -- 5. Arabidopsis fruit development -- 6. Long-distance seed dispersal -- 7. Seed dispersal and crop domestication : shattering, germination and seasonality in evolution under cultivation -- 8. Factors influencing the ripening and quality of fleshy fruits -- 9. Parthenocarpy in crop plants
Includes bibliographical references and index
Keywords: Fruit -- Development; Seeds -- Dispersal